PENINGKATAN HASIL DAN AKTIVITAS BELAJAR PADA MATERI PENELITIAN GEOGRAFI MELALUI MODEL PEMBELAJARAN GUIDED NOTE TAKING KOMBINASI EVERYONE IS A TEACHER HERE - Rusdiyanti, Rusdiyanti (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
This study aims to improve the quality of mastery of the concept of Geography Research material through the strategy of Guided Note Taking a combination of Everyone is a Teacher Here. This research is classroom action research (CAR) which is carried out in two cycles. The subjects in this classroom action research were students of class X IPS 1 SMA Negeri 6 Semarang. In this study, the research subjects were students of class X IPS 1 SMA Negeri 6 Semarang. Class X IPS 1 consists of 36 students with details of 16 boys and 20 girls. Data collection techniques in this study include classroom observations, interviews, distributing questionnaires, formative evaluations, and discussions with partner teachers (collaborators). While the data analysis used in this study is a quantitative and qualitative data analysis technique. The application of the Guided Note Taking model with the combination of Everyone is a Teacher Here can increase the mastery of the concept of geography research material in class X IPS 1 SMA Negeri 6 Semarang with success indicators, namely in the aspect of knowledge experiencing classical learning completeness 75% or with at least good criteria. The results showed that the learning outcomes of mastering the concepts of geography research materials increased. In the first cycle, the number of students who completed was 17 students with a classical completeness percentage of 47.22%. In cycle II, there was an increase in the number of students who completed to 31 students with a classical completeness percentage of 86.11%. Student learning activities also increased. An increase from only 15 students actively asking questions during the first cycle of action learning process to 29 students actively asking questions in the second cycle of action learning process. The activity of answering questions increased from 19 active students to 26 active students answering questions in the learning process in the second cycle of action. The activity of doing assignments increased from 19 active students to 26 students actively working on assignments in the learning process in the second cycle of action. Based on the results of the analysis of action research in cycle I and cycle II, it can be concluded that the Guide Note Taking model of the combination of Everyone is a Teacher Here on the mastery of geography research material in class X IPS 1 SMA Negeri 6 Semarang can improve student learning outcomes.